Sunspot Observations on 10 and 11 February 1917: A Case Study in Collating Known and Previously Undocumented Records. Issue 11 (7th November 2018) - Willis, D. M.; Wilkinson, J.; Scott, C. J.; Wild, M. N.; Stephenson, F. R.; Hayakawa, H.; Brugge, R.; Macdonald, L. T.
Abstract: An extensive investigation of ships' logs, as part of the Old Weather citizen‐science project, identified a sunspot observation made from HMS Hilary on 10 February 1917. This sunspot record was accompanied by detailed meteorological records that have enabled a reconstruction of the conditions under which the observation was made (overcast with detached clouds). Although there is no incontrovertible evidence that this was an unaided‐eye observation, comparison with an unaided‐eye observation recorded on the 11 February 1917 in a local treatise from Hénán province in China confirms that this sunspot group was visible to the unaided eye. White‐light photographs from the Dehra Dun Observatory confirm the detailed description of the sunspot group provided by the naval observer. Moreover, comparisons with tabular data published by the Royal Observatory, Greenwich, confirm the statement that this was an unusually large sunspot group. Indeed, on 11 February 1917 the area of the sunspot group was greater than the area of any sunspot group recorded previously at the Royal Observatory, Greenwich. A comparison with a modern unaided‐eye observation confirms that it is possible to observe sunspots under meteorological conditions similar to those experienced on‐board HMS Hilary. Key Points: We present a previously undocumented observation of a large sunspot group for which the local meteorological conditions are known An unaided‐eye sunspot observation was recorded in China on the following day Contemporary photographic and tabular data corroborate these observations